Resistance to insulin and high altitude. - Castillo Sayán, Oscar (2015)
In this article initial characteristics allowing knowledge of insulin resistance are described. High altitude dwellers show lower basal and postprandial glycemia and no differences in insulinemia compared with sea level dwellers. Incidence of diabetes mellitus is lower at high altitude. Finally studies in sea level residents under both acute natural hypoxia and simulated hypobaric chamber-intermittent hypoxia are presented.